2005
DOI: 10.1088/0264-9381/22/14/012
|View full text |Cite
|
Sign up to set email alerts
|

Constraints from cosmic rays on non-systematic Lorentz violation

Abstract: Abstract.In this article we analyze the radiation loss from a high energy cosmic ray proton propagating in a spacetime with non-systematic Lorentz violation. From an effective field theory perspective we illuminate flaws in previous attempts that use threshold approaches to analyze this problem. We argue that in general such approaches are of rather limited use when dealing with non-systematic Lorentz violating scenarios. The main issues we raise are a) the limited applicability of threshold energy conservatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In this respect I should bring to the attention of my readers the studies of non-systematic effects for ultra-high-energy cosmic rays reported in Refs. [37, 310, 106]. …”
Section: Other Areas Of Uv Quantum-spacetime Phenomenologymentioning
confidence: 99%
“…In this respect I should bring to the attention of my readers the studies of non-systematic effects for ultra-high-energy cosmic rays reported in Refs. [37, 310, 106]. …”
Section: Other Areas Of Uv Quantum-spacetime Phenomenologymentioning
confidence: 99%
“…Note, though, that the symmetry violations in this scenario vary rapidly and essentially stochastically in both space and time. Such "nonsystematic" Lorentz violations are harder to study, but there is evidence that they lead to much weaker observational constraints [59].…”
Section: What Next?mentioning
confidence: 99%
“…One must worry about experimental implications of the resulting violation of Lorentz invariance. But this violation is "nonsystematic"-its parameters vary rapidly in space and timeand such phenomena seem much harder to detect than "systematic" violations [43].…”
Section: The Short Distance Wheeler-dewitt Equationmentioning
confidence: 99%